Migrant background and access to Vocational Education in Germany : self-selection, discrimination, or both? - Tjaden, Jasper Dag [Verfasser] (My University, 2017)
Germany’s Vocational Education and Training (VET) sector is the major channel for the integration of a growing number of students with a migrant background - a group that is overrepresented among non-university school tracks leading towards VET. However, their participation in VET is lower compared to Germans. I argue that previous studies have neglected the role of educational preferences in explaining these disparities. Building on the literature on secondary effects of ethnic origin, I test whether migrants self-select into academic tracks to pursue higher academic qualifications and to what extent this selection explains ethnic inequality in VET access. Using a longitudinal sample of students at the end of lower secondary education (NEPS, N=6247), this study shows that self-selection accounts for 40% of ethnic disparities in VET access. However, further analysis reveals that self-selection at this stage should be understood as complementary to, rather than competing with, alternative explanations, such as discrimination. Implications for research and policy are discussed. (Author's abstract ; BIBB-Doku)

Die Berufsausbildung hat zentrale Bedeutung für die Integration Jugendlicher mit Migrationshintergrund, die häufiger an nicht-gymnasialen Schulformen vertreten sind. Bisherige Befunde deuten darauf hin, dass Jugendliche mit Migrationshintergrund beim Zugang in die Berufsausbildung benachteiligt sind. Die vorliegende Studie untersucht die Bedeutung von gruppenspezifischer Selbstselektion für den Übergang in eine Berufsausbildung. Die Ergebnisse auf Grundlage der NEPS-Längsschnittdaten (N=6247) zeigen, dass 40 Prozent der ethnischen Unterschiede an dieser Schwelle durch Selbstselektionsprozesse erklärt werden können. Zusätzliche Analysen ergeben jedoch, dass Selbstselektion als komplementär und nicht rivalisierend zu anderen Erklärungsansätzen, insbesondere Diskriminierung, verstanden werden sollte. (Autorenreferat; BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 1.3.2.1 Zugänge; P 1.5 Migranten; P 1.1 Jugendliche; Migrant; Ausländischer Jugendlicher; Berufsausbildung; Berufseinmündung; Diskriminierung; Benachteiligung; Ausbildungswunsch